2017
DOI: 10.3354/dao03081
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal helminth fauna of the shortfin mako Isurus oxyrinchus (Elasmobranchii: Lamnidae) in the northeast Atlantic Ocean

Abstract: Large oceanic sharks represent a suitable model to investigate the influence of a host's oceanic conditions on the structure of its helminth communities. In this study, we describe the intestinal helminth fauna, and investigate determinants of infracommunity structure, in 39 specimens of shortfin mako Isurus oxyrinchus collected in the NE Atlantic. Six cestode species were found in the spiral valve of makos: 3 are typical from lamnid sharks, namely, gravid specimens of Clistobothrium montaukensis, Gymnorhynchu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…To the best of our knowledge, only G. gigas has to date been reported from the Mediterranean basin in the swordfish Xiphias gladius Linnaeus, 1758, the Ray's bream Brama brama (Bonnaterre, 1788), and the silver scabbardfish Lepidopus caudatus (Euphrasen, 1788) (49,50). Gymnorhynchus isuri is known from the north, southwestern, and northeast Atlantic and the Tasmanian Sea in the southwestern Pacific, infecting the shortfin mako Isurus oxyrinchus Rafinesque, 1810 and the blue shark Prionace glauca (Linnaeus, 1758) (30,51,52), and no record exists of G. isuri in Mola species anywhere.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only G. gigas has to date been reported from the Mediterranean basin in the swordfish Xiphias gladius Linnaeus, 1758, the Ray's bream Brama brama (Bonnaterre, 1788), and the silver scabbardfish Lepidopus caudatus (Euphrasen, 1788) (49,50). Gymnorhynchus isuri is known from the north, southwestern, and northeast Atlantic and the Tasmanian Sea in the southwestern Pacific, infecting the shortfin mako Isurus oxyrinchus Rafinesque, 1810 and the blue shark Prionace glauca (Linnaeus, 1758) (30,51,52), and no record exists of G. isuri in Mola species anywhere.…”
Section: Discussionmentioning
confidence: 99%
“…The same author also described for the first time the species C. montaukensis from the spiral intestine of the shortfin mako shark ( Isurus oxyrinchus ) [ 44 ]. Subsequent studies confirmed the occurrence of C. montaukensis in shortfin mako [ 48 ] and of C. carcharodoni in the great white shark [ 37 ], while, as mentioned, a specific identification could not be achieved for the specimens identified as C. cf. montaukensis found in the porbeagle Lamna nasus [ 36 ].…”
Section: Resultsmentioning
confidence: 81%
“…We interpret that these immature forms are likely specific to other elasmobranchs and do not reproduce in blue sharks; thus, they could be considered as accidental parasites such as, for example, Anisakis spp. are in other sharks (Penadés-Suay et al, 2017). The degree of preservation of samples of the remaining tapeworm taxa, all containing adults, allowed reliable specific identifications (see below) except for Scyphophyllidium sp.…”
Section: Discussionmentioning
confidence: 99%
“…To globally compare the infracommunity diversity and composition of cestode faunas infecting blue sharks around the world, we searched all parasitological surveys for which at least the prevalence of all tapeworm taxa found in the intestine was reported. These surveys generally did not provide data on mean species richness per host; thus we calculated this parameter by summing up prevalence (expressed as decimals) of all intestinal tapeworm taxa in each sample (Penadés-Suay et al ., 2017). Differences of prevalence of specific taxa among localities were tested with exact Chi-square tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation